2017
DOI: 10.1016/j.jid.2017.07.832
|View full text |Cite
|
Sign up to set email alerts
|

Associations of MC1R Genotype and Patient Phenotypes with BRAF and NRAS Mutations in Melanoma

Abstract: Associations of MC1R with BRAF mutations in melanoma have been inconsistent between studies. We sought to determine for 1227 participants in the international population-based Genes, Environment and Melanoma (GEM) study whether MC1R and phenotypes were associated with melanoma BRAF/NRAS subtypes. We used logistic regression adjusted by age, sex, and study design features and examined effect modifications. BRAF+ were associated with younger age, blond/light brown hair, increased nevi, and less freckling and NRA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 51 publications
1
11
0
1
Order By: Relevance
“…Many of these variants are in gene regions associated with pigmentation, such as TYRP1, TYR, HERC2/OCA2, SLC45A2 , and ASIP ; nevi, such as PLA2G6, MTAP , and NID1 ; or both, such as IRF4 , while others are in genes, including ATM, MX2, PARP1, ARNT , and CASP8 , not associated with melanoma-risk phenotypes (Amos et al, 2011, Barrett et al, 2011, Bishop et al, 2009, Fernandez et al, 2008, Gudbjartsson et al, 2008, Han et al, 2008, Jannot et al, 2005, Law et al, 2012, Macgregor et al, 2011, Nan et al, 2011, Zhang et al, 2012). In parallel but separate studies, we and Hacker et al found that increased number of nevi was associated with melanoma BRAF V600E and V600K subtypes (Hacker et al, 2016, Thomas et al, 2007, Thomas et al, 2017), and we found that BRAF V600E was associated with blond/light brown hair and BRAF V600K with less freckling (Thomas et al, 2017). MC1R has been inconsistently associated with BRAF V600E cases (Fargnoli et al, 2008, Hacker et al, 2010, Hacker et al, 2013, Hacker et al, 2016, Landi et al, 2006, Thomas et al, 2010a).…”
Section: Introductionsupporting
confidence: 75%
See 4 more Smart Citations
“…Many of these variants are in gene regions associated with pigmentation, such as TYRP1, TYR, HERC2/OCA2, SLC45A2 , and ASIP ; nevi, such as PLA2G6, MTAP , and NID1 ; or both, such as IRF4 , while others are in genes, including ATM, MX2, PARP1, ARNT , and CASP8 , not associated with melanoma-risk phenotypes (Amos et al, 2011, Barrett et al, 2011, Bishop et al, 2009, Fernandez et al, 2008, Gudbjartsson et al, 2008, Han et al, 2008, Jannot et al, 2005, Law et al, 2012, Macgregor et al, 2011, Nan et al, 2011, Zhang et al, 2012). In parallel but separate studies, we and Hacker et al found that increased number of nevi was associated with melanoma BRAF V600E and V600K subtypes (Hacker et al, 2016, Thomas et al, 2007, Thomas et al, 2017), and we found that BRAF V600E was associated with blond/light brown hair and BRAF V600K with less freckling (Thomas et al, 2017). MC1R has been inconsistently associated with BRAF V600E cases (Fargnoli et al, 2008, Hacker et al, 2010, Hacker et al, 2013, Hacker et al, 2016, Landi et al, 2006, Thomas et al, 2010a).…”
Section: Introductionsupporting
confidence: 75%
“…We, like others (Duffy et al, 2010a, Duffy et al, 2010b, Han et al, 2008, Zhang et al, 2013), found rs12203592*T to be associated with fewer nevi, darker hair color, and increased freckles. Previously, we reported increased nevi were associated with BRAF V600E and V600K; lighter hair color with BRAF V600E and decreased freckling with BRAF V600K compared to WT melanoma (Thomas et al, 2017). Hacker et al also found increased nevi to be associated with BRAF V600E and V600K vs. WT melanoma (Hacker et al, 2016).…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations